Labour, Mobility and Informal Practices in Russia, Central Asia and Eastern Europe Power, Institutions and Mobile Actors in Transnational Space - Turaeva, Rano; Urinboyev, Rustamjon (BASEES/Routledge Series on Russian and East European Studies, 2021)
This book explores the daily survival strategies of people within the context of failed states, flourishing informal economies, legal uncertainty, increased mobility, and globalization, where many people, who are forced by the circumstances to be innovative and transnational, have found their niches outside formal processes and structures. The book provides a thorough theoretical introduction to the link between labour mobility and informality and comprises convincing case studies from a wide range of post-socialist countries. Overall, it highlights the importance of trust, transnational networks, and digital technologies in settings where the rules governing economic and social activities of mobile workers are often unclear and flexible.